First Trimester Screening for Preeclampsia: An Asian Perspective - Sakita Moungmaithong; Xueqin Wang; Angela S.T. Tai; Qiaoli Feng; Daljit Sahota; Tak Yeung Leung; Liona C. Poon; Dandan Shi (Wolters Kluwer Health, 2021)
Abstract. Preeclampsia (PE) is one of the leading causes of maternal and perinatal morbidity and mortality worldwide. This disorder has profound short-term and long-term impacts on both the affected woman's and her child's health. Early-onset PE requiring preterm delivery (preterm PE) is of particular importance because it is associated with a higher risk of adverse pregnancy outcomes than term PE. First trimester screening model developed by the Fetal Medicine Foundation (FMF), which uses Bayes-theorem to combine maternal characteristics and medical history together with measurements of mean arterial pressure, uterine artery pulsatility index, and serum placental growth factor, has been proven to be effective and have superior screening performance to that of traditional risk factor-based approach for the prediction of PE. Identification of high risk pregnant women for preterm PE and giving aspirin prophylaxis before 16th week of gestation would reduce the incidence of preterm PE. In Asia, although the prevalence of PE is slightly lower than the global estimation, early screening and prevention of this life-threatening condition is still crucial. The FMF Bayes-theorem based screening method has been validated in a large-scale prospective Asia-wide study and revealed that the first trimester triple test achieves the highest detection rate, compared with the traditional risk factor-based approaches, and that the screening performance is comparable to the published data from the FMF in East Asian women. However, in order to achieve optimal screening performance, the key is to establish standardized methods for biomarker measurements and regular biomarker quality assessment, as each biomarker is susceptible to inaccurate measurement, thus affecting performance of screening. Furthermore, it is of great importance to emphasize that the optimal preventive effect of aspirin on preterm PE is clearly associated with good compliance to treatment. In conclusion, global implementation of an effective first trimester "screen and prevent" program for preterm PE would provide the opportunity to reduce the risk of both short-term maternal and perinatal morbidity and mortality, with the possibility of intergenerational prevention of future chronic diseases for both the mother and her offspring.